The influence of workload, work stress and work environment on turnover intention in the Herbal liquid production department - Basar, Muhamad Saepul; Supiyadi, Dedi (Junal Ilmu Manajemen, 2024)
The study aims to determine the influence of the variable Workload, Work Stress and the environment on Turnover Intention. It aims to determine the main factors that affect the turnover intentions in. This research uses census sampling technique because limited population, namely all employees totaling 33 people. The resulting regression model is expressed as: Y = 11,970 + 0.436(X1) + 0.287(X2) + 0.461(X3), where the validity and reliability of the indicator are guaranteed. The model is in line with classical assumptions, emphasizing the dominant role of workload (X1) with a coefficient of 0.436, followed by work stress (X2) at 0.287. Then followed the variable work environment (X3) at 0,461 results showed that the combined influence of workload, work stress and work environment had a significant effect on turnover intention (40,944), thus justifying the research hypothesis. Correlation partial between workload(X1), work stress(X2), work environment (X3) and turnover intention (Y) of 0.809 (80.9%). R Square underscores the strong impact of workload(X1) and work stress (X2) and work environment (X3) on turnover intention at (Y) of 0.809 (80.9%). In conclusion, this study underscores the roles that must be considered by important companies namely workload, apes stress and work environment in forming employee turnover intention.